Evaluation of peak flow design criterion for sewerage system in Taman Mahkota - Loo, Pei Wen (2017)
The peak flow factor design criterion is one of the important elements in the design of sewerage systems in Malaysia. The design of sewerage systems is related to the analysis of flow characteristics. A sewerage system should be designed based on the most critical flow rate. Sewerage system design may become incorrect if the analysis of flow characteristics is not carried out. The purpose of this research is to verify the suitable design criterion for sewerage systems as recommended in Malaysia Standard 1228:1991. This research also aims to study the effect of rainfall on sewerage flow pattern and analyse the flow characteristics in the sewerage system. In this research study, the design criterion for sewerage system was investigated. The investigation was carried out on a selected manhole located in the sewerage treatment plant at Taman Mahkota where field monitoring of sewerage flows was conducted. ISCO 2150 Area-Velocity Flow Meter was used to collect the flow rate and Flowlink 5.1 software was used for data retrieval as well as graph display. Calibration of the flow meter was done in the Hydraulics and Hydrology Laboratory of UMP Gambang. The study duration was from 1 March 2017, 11.00 am to 23 May 2017, 11.59 pm. Each set of data consists of sewerage flow readings every five minutes for the duration of two weeks by using the Area-Velocity method. The same data measurement interval was applied to the rainfall data, collected through an ISCO 674 Rain Gauge also located within the sewerage treatment plant at Taman Mahkota. From the results obtained, the parameters investigated will be compared to their respective value stated in the Malaysia Standard 1228:1991. The value of average actual per capita flow in this research was 0.375 m3/day/person which is 66.7% higher than the per capita flow stated in MS 1228:1991 having a value of 0.225 m3/day/person. On the other hand, the value of average peak flow factor design criterion in this study was 2.9, 38.3% smaller than the design criterion 4.7 mentioned in MS 1228:1991. After the analysis of the results, it can be concluded that the flow characteristics in the sewerage system at Taman Mahkota is sufficient to serve the population equivalent in the study.